Thematic Teaching Materials Based on Riau Local Wisdom - Dewi, Nina Ardianti; Ramadan, Zaka Hadikusuma (Journal of Education Technology, 2021)
The current teaching materials used by teachers are still very concerned where the teaching materials used are the same as student books and the teaching materials used by students and teachers are still general or national in nature which has not been integrated with local wisdom. This causes students to have difficulty understanding the material that affects learning outcomes. The purpose of this research is to create thematic teaching materials based on Riau's local wisdom. The type of research conducted is R&D with the ADDIE model. However, only 3 stages (analyze, Design, and Development) were carried out. The subjects of this study were 6 experts, consisting of 2 material experts, 2 linguists, and 2 design experts, and fourth-grade elementary school students. Data collection methods used are interviews and validation sheets. The analysis carried out is a qualitative and quantitative analysis of interview data and validation sheets. The results of the study stated that thematic teaching materials based on Riau's local wisdom were feasible from the aspect of material, language, and design with an average score of 89.33% with very valid categories. So, thematic teaching materials based on Riau local wisdom are feasible to use.